2001
DOI: 10.1002/mus.1068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiotrophin‐1 (CT‐1) in a mouse motor neuron disease

Abstract: Cardiotrophin-1 (CT-1) has potent survival-promoting effects on motor neurons in vitro and in vivo and may be effective in treating motor neuron diseases (MND). We investigated the effects of CT-1 treatment in wobbler mouse MND. Wobbler mice were randomly assigned to receive subcutaneously injected CT-1 (1 mg/kg, n = 18, in two experiments) or vehicle (n = 18, in two experiments) daily, 6 times/week for 4 weeks after clinical diagnosis at age 3 to 4 weeks. Cardiotrophin-1 treatment prevented deterioration in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
(46 reference statements)
1
17
0
1
Order By: Relevance
“…Its receptor consists of a heterodimer made of glycoprotein 130 (GP130) receptor and leukaemia inhibitory factor receptor (LIFR), together with a yet to be described third component [5]. It is also known that CT-1 has beneficial effects in several tissues, such as motoneurons, by protecting them from apoptosis or by participating in regeneration mechanisms [6]. Recent studies have reported the protective role of CT-1 in the liver; CT-1 is upregulated during liver regeneration and exerts anti-apoptotic effects on hepatocytes [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its receptor consists of a heterodimer made of glycoprotein 130 (GP130) receptor and leukaemia inhibitory factor receptor (LIFR), together with a yet to be described third component [5]. It is also known that CT-1 has beneficial effects in several tissues, such as motoneurons, by protecting them from apoptosis or by participating in regeneration mechanisms [6]. Recent studies have reported the protective role of CT-1 in the liver; CT-1 is upregulated during liver regeneration and exerts anti-apoptotic effects on hepatocytes [7].…”
Section: Introductionmentioning
confidence: 99%
“…CT-1 also provided therapeutic benefit in both functional and morphological parameters in a mouse model of spinal muscular atrophy (SMA) [79,80]. Furthermore, adenovirus-mediated gene transfer of CT-1 or the administration of rCT-1 delayed neurogenic muscular atrophy and progressive neuromuscular deficiency in an experimental model of amyotrophic lateral sclerosis (ALS) [79,81]. Finally, adenoviral CT-1 gene transfer into the injured cord promoted survival and regeneration of rubrospinalneurons in adult rats [82] and promyelinating effects of CT-1 have been demonstrated in vitro by Stankoff et al [83].…”
Section: Nervous Systemmentioning
confidence: 98%
“…CT-1 is the fi rst bona fi de muscle-derived neurotrophic factor to be identifi ed that is required for the survival of subgroups of developing motoneurons 46 . It was concluded that CT-1 exerts myotrophic eff ects as well as neurotrophic eff ects in a mouse model of spontaneous moto neuron disease (MND), a fi nding that has potential therapeutic implications for human MND 51 . Summary of consequences between CT-1 and some additive organ systems and diseases are displayed below (Table 3).…”
Section: Cancermentioning
confidence: 99%